Phenomenological Study of Patient Experiences with Metabolic Syndrome - Nimas Zuhrufana; Okti Sri Purwanti (GLOBAL HEALTH SCIENCE GROUP, 2026)
Metabolic syndrome is a cluster of interrelated metabolic risk factors that have the potential to cause chronic complications such as type 2 diabetes mellitus and cardiovascular disease. This condition affects not only physical aspects but also the psychological and social dimensions of patients. This study aimed to explore the experiences of patients with metabolic syndrome in their daily lives after being diagnosed. A qualitative approach with a phenomenological method was employed to explore and understand the lived experiences of patients with metabolic syndrome. Data were collected through Focus Group Discussion (FGD) and observations involving eight patients aged 56-60 years diagnosed with metabolic syndrome (seven women and one man), each presenting at least three diagnostic components. Data were analyzed using the Miles and Huberman Model, which includes data reduction, data display, and conclusion drawing/verification. Five main themes were identified: (1) initial post-diagnosis experiences, including denial and anxiety; (2) the impact of metabolic syndrome on physical and psychological conditions; (3) family support in emotional, functional, and acceptance forms; (4) adaptation and coping, consisting of self-initiated efforts, treatment adherence, and following healthcare professionals’ recommendations; and (5) life changes after diagnosis, including lifestyle modification, spiritual strengthening, challenges, and the formation of new habits. Patients with metabolic syndrome undergo complex emotional and adaptive processes. Family and healthcare professional support play important roles in helping patients adjust to this chronic condition. These findings contribute to the development of nursing practice based on a holistic bio-psycho-socio-spiritual approach.